Planning in the front end of flagship projects post-disaster : a Canterbury earthquake study : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Construction Management at Massey University, Albany, New Zealand - Rodrigo, Witharanage Lourdes Niransha (Massey University, 2022)
In the recent past, governments around the world have been using large public-funded projects to rebuild their disaster-stricken cities. Large public-builds, better known as flagship projects, have come under scrutiny due to unfavourable project outcomes. The continuity to under-deliver expected outcomes leaves a question about the relevance of flagship projects. Governments around the world continue to invest millions of taxpayer money into large builds. Marysville - a rural town in Victoria, Australia, spent a similar proportion on flagship projects to Christchurch following the Black-Saturday bushfires. Flagship projects post-disaster rarely attract favourable attention. There has been no previous research that explores the outcomes or the root cause of the negative impacts of flagship projects. Ten years post-disaster Marysville flagship projects have not been assessed to check the outcomes against objectives. Driven by the lack of research into flagship project outcomes and their causes, the researcher intends to understand how planning in the front end affects flagship projects in post-disaster rebuilding. The findings will be used to produce a set of guidelines for the planning of future post-disaster flagship projects. The researcher intends to assist government planners in determining if flagship projects would support rebuilding post-disaster by following the guidelines generated using the data of this study. The researcher used a case study approach to fulfill the research aim. A pilot study in Marysville, Australia, using a Grounded Theory approach, revealed that most factors that cause adverse project outcomes are linked to the planning in the front end. The study findings showed that top-level governance arrangements, early planning, and stakeholder management in Front-End Planning have a significant impact on project outcomes. A data-driven model obtained through the analysis formed the basis of the main study. The main literature study was conducted in phases to eliminate bias that could potentially affect Grounded Theory data analysis. The process revealed that pilot study data influenced a revision to the traditional Font-End Planning process. Marysville pilot study revealed that government project planning officials spent time understanding the situation created by the disaster. This activity appeared ahead of the feasibility phase. A modified version of the model included pre-feasibility, feasibility, concept, and detailed scope stages as phases of the Front-End Planning process. The findings informed the differences between routine and post-disaster public projects in the Front end Planning process. The data suggested that Stakeholder Management is a cross-phase activity starting at inception and continues right through to the detailed scope stage and beyond. The main research study was focused on three flagship projects in the Central Business District of Christchurch. The city faced a devastating sequence of earthquakes in 2010-2011 that had scrapped the city of its key buildings. The government planning officials put in place a strategy to rebuild through 17 flagship projects. The researcher adopted a qualitative method that used face-to-face interviewer data to explore three projects to achieve research objectives. The FEP process criteria identified through the pilot study and the previous literature were then applied to the case studies. The researcher adopted a qualitative study approach to construct the theory and used semi-structured face-to-face interviews as the data collection method. Thirty-four expert respondents were interviewed. The interviewees covered all major stakeholder categories for flagship projects in Christchurch, and they belonged to the highest level of decision-makers in their organisations, except for the frequent users of the public facilities in question. The data gathered through the case studies revealed that the projects that more or less followed all of the proposed steps in the front-end planning process had better project outcomes. Some of the adverse outcomes of the projects that followed the FEP process thoroughly still had some negative impacts. The negative impacts were caused by external factors outside of the control of the project owners. Governance at the portfolio level seems to have a lesser effect on projects that were fully Crown-funded. Large projects that allow sufficient time for FEP, specifically in the Pre-feasibility phase, feasibility phase, concept phase, and detailed scope phase seem to avoid detrimental project outcomes. A set of planning guidelines for future government planning officials has been formulated based on the evidence of the case studies. The guidelines address all four areas of the FEP process and follow the process revealed within the study. The research fills the gap where Emergency management frameworks/guidelines only consider immediate recovery following large-scale disasters. Unlike other planning guidelines, the guidelines produced as the output of this study appreciates the effect different governance arrangements may have on the planning of large public projects. With an understanding of governance arrangements post-disaster, the guidelines can be altered and used as a guide to inform better decision-making regarding large public builds post-disaster.
Appendices 6 ©2021 Elsevier Ltd. and 7 ©2020 NZBERS were removed for copyright reasons. Appendix 8 is reproduced under a Creative Commons Attribution-ShareAlike 4.0 International (CC BY-SA 4.0) license.
Keywords: Urban renewal; Public buildings; Planning; New Zealand; Christchurch; Christchurch Earthquake, N.Z., 2011; 330408 Strategic, metropolitan and regional planning